DETERMINATION OF ATTENUATION INDEX CURVE "Ri(f)" FOR HOMOGENEOUS DOUBLE LOCKING ELEMENTS - BUZATU G. C.; STAN IVAN F. E.; MIRCEA P.M.; MIRCEA I. (Journal of Sustainable Energy, 2016)
The paper is structured in three parts. In the first part of the paper, are presented some theoretical notions regarding the sound, noise, the sound insulations materials. Also in the first part of the paper are presented some characteristic regarding the insulation materials and there effects. In the second part it is described an calculation example for a homogeneous wall with double structure in order to determine the attenuation index curve "Ri(f)". The example calculation contains 10 steps that must be followed and the final results are presented in table 7 and figure 3. The last part of the paper is represented by conclusions, where the authors tried to explain the importance of the curve "Ri(f)" for reducing the noise in the buildings.